A SHORT REVIEW OF BONGKREKIC ACID IN FOOD SAFETY PERSPECTIVE - Rifqi Ahmad Riyanto (University of Sultan Ageng Tirtayasa, 2019)
Food safety is one of the concern today for consumer and producer of food products. One of its aspect is the availability of dangerous toxin. Bongkrekic acid belongs to foodborne toxin commonly produced by bacteria Burkholderia cocovenenans. This toxin’s name comes from Indonesian local food, tempe bongkrek, and made several outbreaks in Indonesia with casualties. Bongkrekic acid causes lethal food poisoning which is associated with hyperglycemia. Studies of the bacteria and toxin itself had developed the strategies to prevent the outbreaks. Supported by the hygiene and technologies in parts of the world, bongkrekic acid could be considered under control in the perspective of food safety today.